PTH-048 Towards Understanding Psychological Distress in Inflammatory Bowel Disease: A Qualitative Study of Patients and Healthcare Professionals. (17th August 2016) - Fischer, A; Irving, P; Moss-Morris, R; Hughes, LD
Abstract : Introduction: Inflammatory Bowel Diseases (IBD) are chronic inflammatory autoimmune conditions resulting in sickness, diarrhoea, weight loss, abdominal pain and fatigue. Depression and anxiety are high at 21% and 41% respectively resulting in further reduced quality of life. However, most IBD services do not have access to psychological support or dedicated resources for distress. This study aimed to identify modifiable factors associated with the occurrence of distress in IBD to inform a guided self-management intervention. Methods: Semi-structured interviews were carried out with 29 people with IBD (pwIBD) and twelve healthcare professionals. Interviews were audio-recorded and transcribed verbatim. Data were analysed using thematic analysis with elements of grounded theory. Results: A model of factors identified by pwIBD contributing to distress was developed. Themes included; symptoms which can be embarrassing and uncontrollable during flares; unpredictability and progression of IBD, creating uncertainty for the future; social factors including lack of understanding and the negative impact on social relationships; navigating the healthcare system; medical procedures which can be unpleasant and invasive. Some themes were also recognised as being potential buffers to distress such as having good social support and healthcare staff. Healthcare professionals acknowledged their role in holistic care but cited a lack of knowledge and resources to adequately promote psychological support. Conclusion: PwIBD identified areas acting as potential promoters and buffers to distress in IBD which were mostly supported by healthcare professionals. The results were used to inform the content of a self-management intervention targeting psychological distress. Further we seek to develop guidelines for the successful introduction of the intervention into the NHS standard care. Disclosure of Interest: None Declared